2014
DOI: 10.3389/fpsyg.2014.01076
|View full text |Cite
|
Sign up to set email alerts
|

Pickles and ice cream! Food cravings in pregnancy: hypotheses, preliminary evidence, and directions for future research

Abstract: Women in the United States experience an increase in food cravings at two specific times during their life, (1) perimenstrually and (2) prenatally. The prevalence of excess gestational weight gain (GWG) is a growing concern due to its association with adverse health outcomes in both mothers and children. To the extent that prenatal food cravings may be a determinant of energy intake in pregnancy, a better understanding of craving etiology could be crucial in addressing the issue of excessive GWG. This paper re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 159 publications
2
64
0
2
Order By: Relevance
“…Our findings identified several barriers to healthy GWG that have also been suggested by previous research, including the powerful effect of family members and cultural and social norms promoting the desirability of large babies and the need to “eat for two,” 28 the challenge of coping with food cravings during pregnancy, 29,30 and poor food environments, including ubiquitous fast food and unhealthy foods, and lack of transportation. 29 Our findings also corroborate previous reports that a desire to return to a thinner pre-pregnancy weight is a strong motivating factor and may reduce risk for excess GWG, 31,32 that women are motivated to eat healthy for the sake of their babies, 32 and that personal experience with excess GWG and postpartum weight retention during a prior pregnancy is a salient motivator of healthy GWG.…”
Section: Discussionsupporting
confidence: 73%
“…Our findings identified several barriers to healthy GWG that have also been suggested by previous research, including the powerful effect of family members and cultural and social norms promoting the desirability of large babies and the need to “eat for two,” 28 the challenge of coping with food cravings during pregnancy, 29,30 and poor food environments, including ubiquitous fast food and unhealthy foods, and lack of transportation. 29 Our findings also corroborate previous reports that a desire to return to a thinner pre-pregnancy weight is a strong motivating factor and may reduce risk for excess GWG, 31,32 that women are motivated to eat healthy for the sake of their babies, 32 and that personal experience with excess GWG and postpartum weight retention during a prior pregnancy is a salient motivator of healthy GWG.…”
Section: Discussionsupporting
confidence: 73%
“…Thus, it has been shown that malnourished rats could modify their food preferences according to their nutrient deficiency [52]. Additionally, it has been reported that craving during pregnancy may be associated to the nutritional requirements during this specific period of life [53,54]. …”
Section: Discussionmentioning
confidence: 99%
“…This may be due to changes in hormones, senses, or cultural or psychosocial factors (Cooksey, 1995; Hook, 1978; Orloff & Hormes, 2014). Certain foods are reported to cause nausea, a symptom reported by many women early in pregnancy, while later in pregnancy, many women report that foods are craved.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested craving of sweets and soft drinks caused increased gestational weight gain but food cravings were not tested (Renault, et al, 2015). However others have found that food cravings increase during pregnancy (Belzer, Smulian, Lu, & Tepper, 2010; Orloff & Hormes, 2014; Pope, Skinner, & Carruth, 1992) leading to increased food intake and thereby increased gestational weight gain. Food cravings and emotional eating are thought to decrease with mindfulness (May, Andrade, Batey, Berry, & Kavanagh, 2010; Paolini, et al, 2014) but this has not been empirically tested in pregnant women.…”
Section: Introductionmentioning
confidence: 99%